THE IMPACT OF HAMTARO BASKET MEDIA ON STUDENT LEARNING OUTCOMES IN ARITHMETIC OPERATIONS: A Case Study of Class II at Public Elementary School Oepura 4 Kupang - Marianus Djemiu Raho; Amanda Cornelia Naitili; Vera Rosalina Bulu (Journal of Innovative Technologies in Learning and Education, 2024)
This study examines the Effectiveness of Hamtaro Basket Media as an Educational Media to Enhance Second Grade Student Learning in Arithmetic Operation at SDI Bertingkat Oepura 4, Kupang The study is defined as quasi-experimental design, in which, the population was a total 27 students into Experimental group consisting of (13) and Control group consisting of (14). The control group received traditional instruction: no handout, just a textbook and the teacher´s explanation, whereas the experimental group was taught with an interactive learning material (Hamtaro Basket Media). We analyzed data collected using pre- and post-tests, final examinations, and the independent samples T-test was used to find differences in learning outcomes of each group. The results demonstrated an increased of post-test scores was found in members of the experimental group, compared to control group to significant meaning that it is effective to use Hamtaro Basket Media for Improve Conceptual Understanding Students on Arithmetic concepts. Furthermore, students in the experimental group paid more attention and they worked harder during learning so studying process was more interesting for them participating in a two-way communication. In conclusion, these two studies imply that integrating interactive media such as Hamtaro Basket into mathematics instruction would improve student learning outcomes and engagement to a good extent.